2012
DOI: 10.1001/archophthalmol.2012.531
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Ischemic Retinopathy in Adams-Oliver Syndrome

Abstract: Results. As shown in the Table, by comparison with the GG genotype, the TT genotype was associated with very high risk for all types of ARM, with increasing odds ratios according to the severity of ARM (from 4.60 for early ARM1 to 23.63 and 16.15 for late atrophic and neovascular ARM, respectively). By contrast, associations of the different types of ARM with the GT genotype were modest (OR, 1.45-2.47) and reached statistical significance only for early ARM1. Smoking and CFH Y402H remained independently associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 6 publications
(10 reference statements)
0
12
0
3
Order By: Relevance
“…Incomplete retinal vascularization has been reported previously in two patients with AOS, plus we have noted it a third, unreported time. In two of these patients [Patel et al, ‐ patient 1; Peralta‐Calvo et al, ] DOCK6 was analyzed by our group and no mutations were found (data unpublished). Normal retinal vascularization requires intact pericyte function, supporting the hypothesis that pericyte dysfunction plays a key role in the pathogenesis of the AOS vasculopathy [Patel et al, ; Liu et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…Incomplete retinal vascularization has been reported previously in two patients with AOS, plus we have noted it a third, unreported time. In two of these patients [Patel et al, ‐ patient 1; Peralta‐Calvo et al, ] DOCK6 was analyzed by our group and no mutations were found (data unpublished). Normal retinal vascularization requires intact pericyte function, supporting the hypothesis that pericyte dysfunction plays a key role in the pathogenesis of the AOS vasculopathy [Patel et al, ; Liu et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Because early mortality in AOS is common when it is associated with internal organ involvement and/or ophthalmologic manifestations, its retinal associations have not been well-characterized. 3,5,6 The ability to perform clinic-based multimodal fundus imaging in this 13-year-old patient made it possible to comprehensively document some of the retinal manifestations of AOS.…”
Section: Discussionmentioning
confidence: 99%
“…A gravidade das malformações varia de sutil a desabilitante ou com risco de vida; a variabilidade entre membros da mesma família é comum. Apesar de rara, a morbimortalidade grave na AOS geralmente é resultado de hemorragia ou infecção envolvendo grandes e profundas lesões na calota craniana, ou de anomalias cardiovasculares, incluindo malformações cardíacas graves 5 .…”
Section: Manifestações Clínicas E De óRgãos Internosunclassified
“…Embora um mecanismo fisiopatológico claro não tenha sido reconhecido na AOS, um comprometimento vascular em áreas de watershed, com ou sem faixas amnióticas secundárias ou compressão externa durante a gravidez, tem sido sugerida como uma possível origem para AOS 2,6 . É proposto que uma instabilidade geneticamente diminuída dos vasos sanguíneos embrionários e/ou uma regulação anormal do endotélio possam induzir às anomalias relacionadas com a AOS, uma vez que há um comprometimento da vasculogênese sob a forma de perfusão reduzida e isquemia 5,7 .…”
Section: Manifestações Neurológicasunclassified
See 1 more Smart Citation